A self-regulation intervention conducted by class teachers: impact on elementary students’ basic psychological needs and classroom engagement - Cunha, Jennifer; Martins, Juliana; Peseta, Rafaela; Rosário, Pedro (Frontiers in Psychology, 2023)
Literature has reported a decrease in students’ engagement throughout schooling, but more worrying, is that elementary students already show signs of disengagement. This data sets the case to develop interventions at this school level. The narrative-based intervention “Yellow Trials and Tribulations” aimed to promote self-regulation has been proven to positively impact elementary students’ school engagement. Acknowledging that classroom engagement is expected to be more closely related to learning and achievement than school engagement, the current study aims to extend the research of the mentioned intervention on elementary students’ classroom engagement (i.e., behavioral, emotional, cognitive, and agentic dimensions), as well as on basic psychological needs (i.e., perceived autonomy, competence, and relatedness) – an antecedent of students’ engagement. The current intervention was implemented by 4th-grade class teachers trained for that purpose and was assessed following a quasi-experimental design with pretest and posttest data collection. Participants were 90 students in the experimental group, and 91 in the comparison group. A multivariate analysis of variance with repeated measures was run for each construct. At the end of the intervention, children in the experimental group reported higher perceived competence and classroom engagement (all dimensions) than their counterparts in the comparison group (small and medium effect sizes were found). No follow-up was conducted to examine whether the intervention effects were long-lasting. Results are expected to support researchers’ and educators’ efforts to effectively implement the intervention, and maximize its benefits to students. For example, extra efforts could be made to help implementers better respond to students’ psychological needs (in this case, perceived autonomy and relatedness), and consequently increase classroom engagement (especially behavioral and emotional engagement, which revealed lower effect sizes).